Perspectives on the concepts of futuristic mineral concentration using microscopic robots. Issue 5 (2nd November 2021) - Gomez-Flores, Allan; Kim, Hyunjung
ABSTRACT: There are technologies to fabricate microscopic (milli, micro, and nano) robots at present, and although their large−scale applications in the field of science remain under development, the technology progress is promising. Thus, we review the advances in the technology to fabricate microscopic robots and explore the concepts of their application in mineral concentration. Microscopic robots have not been applied yet in unit operations for mineral concentration. Nevertheless, it is envisioned that the ultimate implementation of microscopic robots for mineral concentration should occur in the form of hand sorting. Additionally, possible limitations (e.g., mass−production or computational power) of the concept are provided. Based on our review, we concluded that the reality of this application will not be accomplished soon. This short perspective could be used as a reference for future proof of concept in experimental work.